TTikar Bergerang: The Reflection of Culture And Heritage Of The Saribas Malay, Sarawak - Faridah, Sahari; Rahah, Hasan; Shahren, Ahmad Zaidi Adruce; Shahri, Abdul Rahman; Anna, Durin (Human Resource Management Academic Research Society (HRMARS), 2012)
This paper investigates the indigenous knowledge of mat making and its social context in Malay community of Saribas. It focuses on tikar bergerang in particular. The mat which incorporates open weave, creates a lace impression pattern around the body weave frame. As stated by Awang Azman (2010), material culture’s scholar, there is an urgency to study Sarawak Malay due to a significant dissimilarity between them with the Malay of Peninsular Malaysia in many aspects of local knowledge and heritage. Thus, the aim of this research is to discover the production technology, role and values of tikar bergerang in the Saribas Malay community in Sarawak. Through in-depth interviews with tikar bergerang weavers and observation, the cultural object is analysed using material culture study developed by Fleming (1974). The result indicated that the mat is only intended for important function and perceived as a sacred material object. The mat complex patterns and complicated weaving techniques reflect the idiosyncrasy of Saribas region compared to other parts of Sarawak, the intellectual, indigenous technology and common values shared among its community.